NUTRITIONAL AND TOXICOLOGICAL EVALUATION OF WILD EDIBLE PLANTS FROM NORTH-EAST INDIA: IMPACT OF VARIOUS COOKING METHODS - Seal, Tapan; Chaudhuri, Kausik; Pillai, Basundhara (Food and Feed Research, 2025)
This study aimed to explore the nutritional value, anti-nutritional factors, mineral content, and in vitro toxicity of ten wild edible plants from the North-Eastern region of India, including Meynia laxiflora, Castanopsis indica, Docynia indica, Flemingia vestita, Bauhinia purpurea, Dillenia pentagyna, Diplazium esculentum, Elaeagnus latifolia, Elaeagnus pyriformis, and Fagopyrum cymosum. The impacts of cooking techniques including boiling and microwaving were also investigated in the study.Nutritional analysis assessed fat, protein, fibre, carbohydrate, and mineral content in both raw and cooked samples. The anti-nutritional properties were evaluated by measuring the content of cyanogenic glycosides, oxalates, tannins, saponins, and phytates. In vitro toxicity was assessed through haemolytic assays on rat erythrocytes, cytotoxicity was measured using the MTT assay, and genotoxicity was evaluated using the comet assay.  The findings revealed that both cooking methods reduced ash, fat, mineral content, anti-nutritional factors, and plant toxicity. At the same time, increasing the relative concentration of fibre and carbohydrates due to water loss or the breakdown of other components, the absolute content of these nutrients remained unchanged. Microwave cooking significantly enhanced the measured protein content (p